Occipital region squamous cell carcinoma: A case report and review of literature (Indian Journal of Case Reports, 2020)
Squamous cell carcinoma (SCC) is the second most common form of aggressive skin cancer and is due to exposure of ultraviolet radiation (B), immunosuppression, inflammation (from trauma or burns), and chemicals. In contrast, SCC is uncommon in darker skin individuals, especially those living in Asia. Here, we report the case of a 67-year-old male who presented to us with a complaint of the non-healing lesion over the occipital region for 2 years. A computed tomography head was done and a possibility of distal metastasis was excluded. The patient underwent wide local excision with scalp rotational flap followed by radiotherapy. Although the incidence of SCC is lower in the Indian people, it is important to consider the diagnosis for a suspicious lesion. The correct management of SCC is wide local excision along with flap rotation.